DEVELOPING 4C – BASED HOTS ASSESSMENT TO IMPROVE STUDENTS’ CRITICAL THINKING SKILLS AT GRADE VI ELEMENTARY SCHOOLS IN KUDUS DISTRICTS - Tigas Tri Kurniawan; Santoso Santoso; Sri Utaminingsih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This study aimed to: (1) formulate the development of HOTS assessment design based on 4C to improve students' critical thinking ability in mathematics learning at grade VI elementary schools in Kudus; (2) describe the characteristics of 4C-based HOTS assessment in mathematics learning at grade VI elementary schools in Kudus; and (3) analyze the effectiveness of 4C-based HOTS assessment to improve students' critical thinking ability at grade 6 elementary schools in Kudus. This research utilized research and development (R&D) design. The development design adapted the development model according to Borg & Gall consisting of ten stages. The trial was conducted on 37 students at SD 1 and 2 Gribig as the experimental group, and 36 students at SD 1 and 3 Klumpit as the control group. Data were collected through observations, questionnaires, tests, and interviews. Data of the effectiveness of 4C-based HOTS assessment were analyzed with gain test, t test at a significance level of 0.05. HOTS assessment was developed in the form of HOTS assessment instruments based on 4C with 7 characteristics, including: 1) measuring high-level thinking ability, 2) divergent, 3) using multirepresentation, 4) contextual problem-based, 5) using various forms of questioning, 6) measuring the communication ability, and 7) measuring the ability to work together. 4C-based HOTS assessments were effective to improve students' critical thinking ability and learning outcomes. This was evidenced by an increase in the average score of students' critical thinking ability in the experimental group that was 80.59 with moderate category and an increase in the average score of students’ learning outcomes in the experimental class for 89.05 with a moderate category. Based on the description above, it could be concluded that 4C-based HOTS assessment improved the students’ critical thinking ability at grade 6 elementary schools.